Shared cultural characteristics similarities in Malaysia’s multi-ethnic society - Abu Bakar, Hassan; Mohamad, Bahtiar; Halim, Haslina; Subramaniam, Chandrakantan; Choo, Ling Suan (Taylor & Francis Group, 2018)
The dimension of cultural characteristics is essentially ignored by the growing literature on organizational diversity, focusing on demographic diversity and general perceived similarity instead. This study aims to identify the similarities in cultural characteristics among ethnic groups in Malaysia. Ergo, conducted within the context of interethnic relations in Malaysia based on a phenomenographic approach; thence, found four categories namely the community embeddedness, the survival culture, the conformity culture and the respect culture. These exemplify the interethnic relations based on cultural characteristics and norms similarities. The cultural characteristics similarities between major ethnics in Malaysia in this study are indications of dynamic and interactive exchange occurring between ethnics. The consequences of these findings are discussed and elaborated in this article.